2020
DOI: 10.1021/acsanm.0c00346
|View full text |Cite
|
Sign up to set email alerts
|

TiO2/ZrO2 Nanoparticle Composites for Electrochemical Hydrogen Evolution

Abstract: Composites of different semiconductors are found to show much improved electronic conductivity and decreased charge transfer resistance. In this work, this hypothesis is tested by preparing composite heterostructures of chemically and structurally dissimilar and wide-bandgap semiconductors, titania (TiO2) and zirconia (ZrO2). Herein, the underpotential hydrogen generation ability of the composite nanoparticles is studied for the first time. The dissimilarity in coordination can create charge imbalance once the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…It may also be advantageous to improve performance by taking advantage of the synergistic effects of bimetallic electrocatalysts. Singh et al reported that the B-TiZr-2.5 catalyst has improved HER activity [ 22 ]. It is recognized that the single metal catalyst is not enough to make the HER catalyst active.…”
Section: Introductionmentioning
confidence: 99%
“…It may also be advantageous to improve performance by taking advantage of the synergistic effects of bimetallic electrocatalysts. Singh et al reported that the B-TiZr-2.5 catalyst has improved HER activity [ 22 ]. It is recognized that the single metal catalyst is not enough to make the HER catalyst active.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these challenges, AWE is still the most widely deployed technology for large-scale hydrogen production; the technology can be conducted with nonprecious-metal-based catalysts and requires less expensive components for construction. 9,20,[23][24][25] However, the need…”
Section: Introductionmentioning
confidence: 99%
“…Electrolytic production of hydrogen from water as an alternative energy carrier to fossil fuels has attracted a plethora of attention in the context of sustainability, renewable energy source utilization and green technology . Currently, there are two main types of low‐temperature water electrolysis available for commercial deployment: conventional alkaline water electrolysis (AWE) and proton exchange membrane water electrolysis (PEMWE) .…”
Section: Introductionmentioning
confidence: 99%